Reducing torque pulsations in PMa-SynRM: a way for improving motor performance - Percy R. Viego; Julio R. Gómez; Vladimir Sousa; José P. Monteagudo Yanes; Enrique C. Quispe (Institute of Advanced Engineering and Science, 2021)
This paper aims to evaluate the performance of synchronous reluctance motors assisted by a permanent magnet (PMa-SynRM) focused on efficiency and torque pulsations. PMa-SynRM shows high efficiency and power factor, compared to induction motors (IM), although they have a greater cost. These machines develop relatively high torque ripple, cogging torque, and torque imbalances. Consequently, the electromagnetic torque is reduced, the motor temperature is increased, and mechanical vibrations are induced. The optimal design of the machine structures such as flow barriers, permanent magnets, and stator slots, among others, allow reducing torque pulsations. A comparison is made between different designs of the PMa-SynRM reported in the scientific literature, and the effects on efficiency, torque pulsation, and operating costs are evaluated. A case study on the motor driving the air conditioner blower in a hotel room was made, to determine the best economic variant between IM or PMa-SynRM. A sensitive analysis was made to evaluate several uncertainties. The advantages of using one of the PMa-SynRM analyzed were demonstrated. Also, it was proved that the investment is feasible economically, although NPV and payback are not the best, due to low load factor in inverter-controlled motors in air conditioners.